PHARMACOGNOSTICAL AND PHYSICOCHEMICAL EVALUATION OF AEGLE MARMELOS (L.) CORREA. LEAF EXTRACT. - SAMIDHA M. PAWASKAR; K.C.SASANGAN (International Journal of Pharma and Bio Sciences, 2017)
Plants serve as a vast source for varied phyto-constituents exhibiting varied pharmacological properties. Identifying such potential plants is of significance in medicine. So it becomes necessary to study the pharmacognostic characteristic and physicochemical parameters of the plant before its use in the field of research and also in pharmaceutical formulation. Moreover, it also helps in distinguishing it from other allied species and adulterants. In this connection, the pharmacognostical characteristics of the leaf of Aegle marmelos (L.) Correa. were examined. The macro and microscopical characteristics like, vein islet numbers, palisade ratio, stomatal index (upper and lower surfaces of the leaf) etc were studied. Physicochemical parameters evaluated include ash values, extractive values and loss on drying. These findings will be helpful towards establishing pharmacognostic and physiocochemical standards on identification, purity, quality and classification of the plant, which is gaining relevance in plant drug research.